The role of universities in accelerating the sustainable development goals in Europe - Walter Leal Filho and Javier Sierra and Elizabeth Price and João Henrique Paulino Pires Eustachio and Aliaksandr Novikau and Maria Kirrane and Maria Alzira Pimenta Dinis and Amanda Lange Salvia (Scientific reports, 2024)
The process of implementation of the UN Sustainable Development Goals (SDGs) which were approved by the UN General Assembly in 2015 has not been simple, being influenced by variety of social, economic, and logistical problems. It has also been negatively affected by the COVID-19 pandemic. There are to date no specific studies aimed at assessing the extent to which higher universities institutions in Europe are active in the SDGs implementation process. Departing from this research need, this paper reports on a study aimed at examining the current degree of engagement of European universities in the implementing the SDGs. By using a multi-methods approach, which entails a review of existing documents, a survey involving participants from 22 countries and case studies, the paper maps, documents and disseminates examples of what European universities are doing to implement the SDGs, the challenges they face, and the solutions being deployed to overcome them.
Keywords: Ecology; Environmental social sciences